Utility of CA-125 for diagnosis and prognosis of breast cancer: a systematic review - Zohre Momenimovahed; Afrooz Mazidimoradi; Leila Allahqoli; Zohre Khalajinia; Hamid Salehiniya; Ibrahim Alkatout (Exploration of Targeted Anti-tumor Therapy)
Background: Different tumor markers are utilized in the assessment of breast cancer. The function of these markers in assessing, tracking, and following up on breast cancer has drawn the interest of numerous researchers. Nonetheless, contradictory findings from research continue to raise questions regarding their effectiveness. Consequently, this research was carried out to evaluate the efficacy of carbohydrate antigen-125 (CA-125) in the treatment of breast cancer. Methods: A thorough investigation was performed in the PubMed, Scopus, and Web of Science databases utilizing relevant keywords: CA-125, breast cancer, screening and diagnosis, and Mesh to locate articles published before August 2023 without any time limitations. The analysis included observational studies in English pertinent to the study’s objective, while review articles, case reports, editor letters, comments, and other reports were not considered. Articles were sought, examined, included, and evaluated according to the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-analyses. The EndNote X9 program has been utilized for item management. The review included articles that investigated the predictive function of CA-125 in the screening, diagnosis, and anticipation for the early and proper detection of breast cancer. Results: In the initial search, 1,475 articles were obtained. After screening and eligibility assessment, 33 studies were reviewed. Based on the findings of the studies, CA-125 can play a role in the diagnosis of breast cancer, its type and stage, early detection of recurrence and metastasis, treatment efficiency, prognosis, and survival rate. Discussion: The role of CA-125 as a biomarker for early detection, staging, and monitoring of recurrence and metastasis in breast cancer is still uncertain and needs additional research.